Festejos, liberdade e fé: a irmandade de São Benedito de Itu no século XIX (1861-1888) - Barbi, Rafael José [UNIFESP] (2015)
The aim of this work is to discuss the Brotherhood's of St. Benedict of Itu performance, a brotherhood of captive and black liners within the context of the second half of the nineteenth century. The discussion is based on the document produced by the members of the Brotherhood, in the association archive and also the documentation found in the archives in Itu, São Paulo and Jundiaí. The analysis will be based on two key elements. The first are the celebrations like priority actions for all directors of the brotherhood and to the activities seek to understand how these parties could be identity maintenance tools or cultural aspects of African origin. The second is the performance of the Brotherhood in the pursuit and consolidation of the freedom of his brothers, thus creating a reflection on the limits of performance of the St. Benedict Brotherhood in the social field to his brothers.